Value addition in banana - Jasmin L Rasheed (Department of Processing technology,College of Agriculture, 2005)
The present investigation entitled 'Value addition in banana (Musa spp.)' was carried out to explore the possibility of value addition in banana through development of different food products and to evaluate the suitability of three cultivars viz., Nendran, Red Banana and Palayankodan. Five products namely squash, RTS, puree, fig and fruit bar had been prepared and evaluated. The biochemical, organoleptic and microbiological qualities were observed at the time of preparation as well as during storage. TSS of all the four products were found to be increasing except in puree. In puree TSS decreased with increase in storage period. Acidity of the products increased with increase in storage period except in the case of fig. The total sugars, reducing sugars and non reducing sugars increased during storage in squash, puree, fig and fruit bar while in RTS only reducing sugars were increased during storage. Moisture content in products like puree and fig were found increasing and that in fruit bar was found decreasing during storage.' Other biochemical parameters like vitamin C and total carotenoids were always decreased during storage for all the five products. In the case of carotenoid content there was marked difference in the products made from cultivar Nendran with those of other cultivars. Nendran products had very high total carotenoids compared to the products of other two cultivars. Regarding the organoleptic quality, Red Banana' products were more acceptable with regard to taste and flavour in most of the products. The exceptions were puree and RTS which were prepared with Nendran cultivar. Nendran products maintained an appreciable colour for the products especially in puree. The organoleptic qualities decreased during storage. Bacterial and fungal colonies were found during the later stages of storage. Only fruit bar remained intact for the full term of six months of storage. The lowest shelflife was for R TS.